Perancangan Sistem Penjualan Emas Berbasis Website (Studi Kasus: Toko Emas Rizqi Ciputat Timur, Tangerang Selatan) - Naufal Akmal Maulana; Dennis Putra Nanda; Muhammad Rafli Reinanda (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The development of information technology has encouraged various business sectors to adopt digitalization in business processes in order to improve efficiency and accuracy in data management. Risqi Gold Store is a business engaged in gold buyback transactions that still implements a manual system in recording transactions, determining gold prices, and managing customer data. This manual process creates several problems, such as the risk of calculation errors due to fluctuating gold prices, slow transaction services, and inefficient data storage management. This study aims to design and develop a website-based gold receiving information system to support transaction processes in a more effective, accurate, and integrated manner. The system development method used in this research is the Waterfall method, which includes the stages of requirements analysis, system design, implementation, and testing. The system was developed using PHP as the backend programming language, MySQL as the database management system, and HTML, CSS, and JavaScript as the user interface technologies. The results of this study indicate that the developed system is capable of automatically calculating gold price estimations based on current market prices, accelerating customer service processes, reducing the risk of calculation errors, and improving the security and efficiency of digital transaction data management.